Downregulation of Varicella-Zoster Virus (VZV) Immediate-Early ORF62 Transcription by VZV ORF63 Correlates with Virus Replication In Vitro and with Latency - Hoover, Susan E. (American Society for Microbiology, 2006)
Varicella-zoster virus (VZV) open reading frame 63 (ORF63) protein is expressed during latency in human sensory ganglia. Deletion of ORF63 impairs virus replication in cell culture and establishment of latency in cotton rats. We found that cells infected with a VZV ORF63 deletion mutant yielded low titers of cell-free virus and produced very few enveloped virions detectable by electron microscopy compared with those infected with parental virus. Microarray analysis of cells infected with a recombinant adenovirus expressing ORF63 showed that transcription of few human genes was affected by ORF63; a heat shock 70-kDa protein gene was downregulated, and several histone genes were upregulated. In experiments using VZV transcription arrays, deletion of ORF63 from VZV resulted in a fourfold increase in expression of ORF62, the major viral transcriptional activator. A threefold increase in ORF62 protein was observed in cells infected with the ORF63 deletion mutant compared with those infected with parental virus. Cells infected with ORF63 mutants impaired for replication and latency (J. I. Cohen, T. Krogmann, S. Bontems, C. Sadzot-Delvaux, and L. Pesnicak, J. Virol. 79:5069-5077, 2005) showed an increase in ORF62 transcription compared with those infected with parental virus. In contrast, cells infected with an ORF63 mutant that is not impaired for replication or latency showed ORF62 RNA levels equivalent to those in cells infected with parental virus. The ability of ORF63 to downregulate ORF62 transcription may play an important role in virus replication and latency.